Spuriously Elevated Cardiac Troponin in the Setting of Atypical Chest Pain Presentation: A Diagnostic Conundrum - Kassem, Kamal M. (JACC Case Rep, 2020)
A 47-year-old woman presented with atypical chest pain and a troponin level of 30.15 ng/dl. A detailed diagnostic work-up did not detect an acute myocardial infarction but revealed the presence of heterophile antibodies. Laboratory values need to be interpreted in the context of the clinical picture when test results do not correspond to clinical findings. (Level of Difficulty: Beginner.)